Traços da espiritualidade missionária a partir da América Latina - Vigil, José Ma. (Revista eclesiástica brasileira, 2004)
The author points to and describes those traits that, in his view, are typical of the Latin-American missionary spirituality and inspired by a historical eschatological reading of the Christian revelation. He also lists some attitudes that determine the resulting missionary practice, namely: contemplation, soteriological optimism, penitential posture, institutional detachment, collaboration with other evangelizers, “inculturation”, and respect for the people’s religion.